The Effect of Tax Planning And The Implementation of The Core Tax Administration System on Taxpayer Compliance - Harry Tubagus Ilyas; Sony Devano Devano; Selly Herdianti Herdianti (Eduvest - Journal of Universal Studies, 2025)
This study aims to analyze the influence of tax planning and the implementation of the Core Tax Administration System (CTAS) on taxpayer compliance. While tax planning is considered a legitimate effort to minimize tax liabilities, the results indicate that tax planning does not have a significant direct effect on taxpayer compliance. Conversely, the implementation of CTAS, driven by the digitization of the tax administration system, plays a significant role in enhancing taxpayer compliance by automating processes and providing easier access for taxpayers to fulfill their tax obligations. Path regression analysis reveals that the combination of tax planning and CTAS implementation simultaneously has a positive impact on taxpayer compliance. These findings emphasize the importance of developing an integrated tax system that can optimize state revenue while facilitating taxpayers in fulfilling their obligations. This study recommends that the government continues to advance tax digitization to strengthen taxpayer compliance.